2015 23rd European Signal Processing Conference (EUSIPCO) 2015
DOI: 10.1109/eusipco.2015.7362524
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the nonlinearity degree for polynomial autoregressive processes with RJMCMC

Abstract: Despite the popularity of linear process models in signal and image processing, various real life phenomena exhibit nonlinear characteristics. Compromising between the realistic and computationally heavy nonlinear models and the simplicity of linear estimation methods, linear in the parameters nonlinear models such as polynomial autoregressive (PAR) models have been accessible analytical tools for modelling such phenomena. In this work, we aim to demonstrate the potentials of Reversible Jump Markov Chain Monte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In previous studies [7][8][9][10][11], making an assumption that all model subspaces are equally likely a priori, appears as a natural choice in the absence of real prior information about model orders of an observed data. Given these, we assume that the MA order q, and the nonlinearity degree p are uniformly distributed with upper bounds p max and q max :…”
Section: Bayesian Hierarchy and Priorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies [7][8][9][10][11], making an assumption that all model subspaces are equally likely a priori, appears as a natural choice in the absence of real prior information about model orders of an observed data. Given these, we assume that the MA order q, and the nonlinearity degree p are uniformly distributed with upper bounds p max and q max :…”
Section: Bayesian Hierarchy and Priorsmentioning
confidence: 99%
“…In a previous study [11], we demonstrated the success of RJMCMC algorithm in the estimation of PAR processes with unknown degree of nonlinearity. In this study, we reformulate this PAR model estimation problem for the synthetically generated PMA models.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this paper, the formulation in previous studies [22], [23] has been reconstructed into a general framework which estimates the nonlinearity degree of PARMA models. In addition to the nonlinearity degree, AR and MA orders and all the model coefficients have been estimated at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies [22], [23], we have shown that RJMCMC can be used as a model determination method which performs transitions between linear and nonlinear model spaces for polynomial AR (PAR) and polynomial MA (PMA) models.…”
Section: Introductionmentioning
confidence: 99%